Turning Private Concerns into Public Issues: Mental Retardation and the Parents' Movement in Post-war Greece, c. 1950–80. (19th August 2015) - Kritsotaki, Despo
Abstract: This article explores the history of mental retardation in the context of the parents' movement in Greece between 1950 and 1980, when the fields of child mental health and special education were becoming established. I focus on the first association of parents of children with mental retardation and use the concepts of public sociality and social movement to analyze how this association perceived mental health and normality in children and how it interacted with professionals and the state. Drawing on this case study, I argue that, in the second half of the twentieth century, parents' movements in the Western world adopted a new approach towards mental retardation as a public issue, namely as a problem not just of the individual and the family but of the whole of society, which had to be made socially visible and deserved the state's intervention. In these ways I propose a fresh perspective on the history of mental retardation and the parents' movements beyond Greece on the basis of the shifting boundaries between the public and the private and the politicization of the personal.